The use of arms in wrestling kumite - Ito, S.; Kanosue, K.; Nagashima, K.; Matsumoto, R.; Iteya, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The purpose of wrestling is to take down the opponent. Leg attack is the most important technique to this end and obtain scores (1). The set up is an efficient way to improve the leg attack success rate (2). The situation in which wrestlers push or pull the opponent to execute the set up and leg attacks is defined as kumite. In kumite, wrestlers use arms to gain control over the opponent to break their balance. A wrestler`s stance is usually putting one leg about one foot in front of the other. The hand closest to the opponent is called close hand (CH) and the hand furthest is called far hand (FH). Little is known of the role of each arm in kumite, although coaches and athletes would understand its importance. The purpose of this study is to clarify arm use in kumite to improve wrestlers` performance.